Yard crane dispatching to minimize maximum tardiness of the jobs - Wan, Zhi Yong (2014)
Maritime freight shipping is a key factor in the world’s freight industry. In 2012 alone, over 9 billion tons of cargo was moved via maritime transport. A key factor in this trade is the usage of containers or “containerization”, large weathered steel boxes that allow convenient and efficient storage of goods to be shipped.